2019
DOI: 10.1029/2018jc014539
|View full text |Cite
|
Sign up to set email alerts
|

Coupled North Atlantic Subdecadal Variability in CMIP5 Models

Abstract: The interaction between the atmosphere, specifically the North Atlantic Oscillation, and the North Atlantic Ocean circulation on subdecadal time scale is analyzed in a subset of models participating in the Coupled Model Intercomparison Project phase 5. From preindustrial control runs of at least 500‐year length, we derive anomaly patterns in the atmospheric and ocean circulation and of air‐sea heat exchange. All models simulate a distinct dipolar oceanic overturning anomaly at the subdecadal time scale, with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 44 publications
9
17
0
Order By: Relevance
“…The ingredients of the mechanism presented in Fig. 14 are largely consistent with previous findings on North Atlantic decadal (10-20 year time scale) variability, including the key role of ocean gyre adjustment to variable wind forcing (Grötzner et al 1998;Wu and Liu 2005;Nigam et al 2018), and the importance of meridional overturning circulation anomalies as a response to air-sea heat fluxes in the SPNA (Häkkinen 2000;Martin et al 2019). Consistent with an important role for the AMOC in driving decadal SST variability, the anti-phase SST relationship between the SPNA and Gulf Stream extension region projects well on the observed decadal AMOC fingerprint (Zhang 2008).…”
Section: Summary and Discussion Of The Proposed Mechanismsupporting
confidence: 87%
See 1 more Smart Citation
“…The ingredients of the mechanism presented in Fig. 14 are largely consistent with previous findings on North Atlantic decadal (10-20 year time scale) variability, including the key role of ocean gyre adjustment to variable wind forcing (Grötzner et al 1998;Wu and Liu 2005;Nigam et al 2018), and the importance of meridional overturning circulation anomalies as a response to air-sea heat fluxes in the SPNA (Häkkinen 2000;Martin et al 2019). Consistent with an important role for the AMOC in driving decadal SST variability, the anti-phase SST relationship between the SPNA and Gulf Stream extension region projects well on the observed decadal AMOC fingerprint (Zhang 2008).…”
Section: Summary and Discussion Of The Proposed Mechanismsupporting
confidence: 87%
“…Previous studies have reported a wide range of mechanisms underlying North Atlantic decadal variability (e.g., Grötzner et al 1998;Häkkinen 2000;Eden and Willebrand 2001;Dong and Sutton 2005;Williams et al 2014;Menary et al 2015a;Muir and Fedorov 2017;Nigam et al 2018;Martin et al 2019). The proposed mechanisms differ in the relative roles of ocean circulation changes and atmospheric forcing in setting upper-ocean heat content and SST anomalies, the importance of ocean gyre and overturning circulation, and whether decadal ocean temperature variability is part of a coupled atmosphere-ocean mode of variability or an ocean-only mode.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that winter NAO‐like circulation patterns and associated surface heat and momentum forcing precede North Atlantic Ocean circulation and heat content adjustments as part of a subdecadal coupled system (Martin et al, ; Reintges et al, ). Further, positive heat content anomalies in the subtropical Atlantic can emerge 2–3 years after a strong NAO.…”
Section: A Subdecadal Coupled North Atlantic Climate Systemmentioning
confidence: 99%
“…A significant spectral peak at ~9 years has also been found for the North Atlantic Oscillation (NAO; Da Costa & Verdiere, ). Observations and modeling results indicate an active role of the atmospheric heat and momentum forcing from the winter NAO, together with a delayed effect of the redistribution of North Atlantic water masses on a subdecadal to decadal time scale (Czaja & Marshall, ; Eden & Greatbatch, ; Martin et al, ; Reintges et al, ). Others noted the relative importance of the Arctic sea ice (Deser & Blackmon, ) and remote forcing such as the decadal variations of El Niño/Southern Oscillation (ENSO) with the NAO (Müller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we examined the multi-time-scale feature of SST variability averaged in the North Atlantic as a whole using observational (analysis and reanalysis) datasets. Some previous works have studied the variability of the North Atlantic as a whole but they mostly focused on multidecadal and subdecadal time scales (Álvarez-García et al 2008(Álvarez-García et al , 2011Frankcombe et al 2010;Reintges et al 2017;Martin et al 2019). In fact, as seen from the raw North Atlantic SST (NASST) index (NASSTI; Fig.…”
Section: Introductionmentioning
confidence: 99%